Quantum chrono-topology of nuclear and sub-nuclear reactions - The measurement problem - Syros, C.; Schulz-Mirbach, C.; Raptis, G. (HNPS Advances in Nuclear Physics, 2019)
The conventional tacit assumption that nuclear and sub-nuclear reactions take place in the Newtonian universal time is replaced in the present paper by a time topological space based on the interaction proper time neighbourhood. It is developed and used to solve a problem related to the nuclear reaction theory, the quantum measurement problem. The time topology is disconnected and satisfies the separation axioms of the topological space 3 , . In this topology the V+R Penrose dynamics is implemented by means of a time evolution operator,"?/ .constructed using a quantized version of CSel'fand's theory - the generalized random quantum field theory (QRQFT). As an application the quantum measurement problem solution is presented.